Myelin-oligodendrocyte glycoprotein antibody-associated disease. Issue 9 (September 2021) - Marignier, Romain; Hacohen, Yael; Cobo-Calvo, Alvaro; Pröbstel, Anne-Katrin; Aktas, Orhan; Alexopoulos, Harry; Amato, Maria-Pia; Asgari, Nasrin; Banwell, Brenda; Bennett, Jeffrey; Brilot, Fabienne; Capobianco, Marco; et al.
Summary: Myelin-oligodendrocyte glycoprotein antibody-associated disease (MOGAD) is a recently identified autoimmune disorder that presents in both adults and children as CNS demyelination. Although there are clinical phenotypic overlaps between MOGAD, multiple sclerosis, and aquaporin-4 antibody-associated neuromyelitis optica spectrum disorder (NMOSD) cumulative biological, clinical, and pathological evidence discriminates between these conditions. Patients should not be diagnosed with multiple sclerosis or NMOSD if they have anti-MOG antibodies in their serum. However, many questions related to the clinical characterisation of MOGAD and pathogenetic role of MOG antibodies are still unanswered. Furthermore, therapy is mainly based on standard protocols for aquaporin-4 antibody-associated NMOSD and multiple sclerosis, and more evidence is needed regarding how and when to treat patients with MOGAD.